NEW MEDICINAL FORM IN TREATMENT OF BRONCHIAL ASTHMA: FIXED COMBINATION OF FORMOTEROL AND BECLOMETASONE - O.I. Simonova ("Paediatrician" Publishers LLC, 2010)
The article describes advantages of new combined drug Foster - formoterol (6 ?g) and beclometasone) (100 ?g) in treatment of patients with bronchial asthma. It was marked that the drug is based on original delivery technology «Modulite» allowing creation an aerosol with extra fine-dispersed particles. Due to this technology medication passes into airways deeper and evenly, resulting in decrease of dose of medication, necessary for achievement of clinical effect and significantly lessen the risk of adverse effects.Key words: children, bronchial asthma, fixed combination, formoterol, beclometasone.(Voprosy sovremennoi pediatrii - Current Pediatrics. - 2010;9(3):136-139)